Ways to improve the technology for producing axle steel grades - O. P. Krasyuk; I. O. Pisarenko; V. S. Puteev (Литьë и металлургия)
This article presents the results of efforts to improve the technology for producing continuously cast billets measuring 300×400 mm, intended for manufacturing railway axles. The necessary technological operations, modes, and conditions required to meet the specified quality requirements for the macroand microstructure of continuously cast billets have been identified. A wide range of modern research methods was employed during the study, including various techniques for assessing the macrostructure of continuously cast billets, metallographic analyses using optical and electron microscopy.